2015
DOI: 10.1007/s00701-015-2382-z
|View full text |Cite
|
Sign up to set email alerts
|

Endonasal ultrasonography-assisted neuroendoscopic transsphenoidal surgery

Abstract: We report endonasal ultrasonography (US)-assisted neuroendoscopic transsphenoidal surgery (TSS) in seven patients. With sagittal and coronal US images, internal carotid arteries, anterior cerebral arteries, residual tumor, and lateral ventricles were recognized, and the tumors were removed without leakage of cerebrospinal fluid in patients with pituitary adenoma. US images clearly depicted the carotid arteries, anterior cerebral arteries, middle cerebral arteries, chiasmatic cistern, and residual tumor. Endona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…The new developed instrumentations include high definition 3D endoscopic system, 10) endoscopic augmented reality navigation system, 62) ultrasonography-assisted endoscope, 63) the indocyanine green fluorescence endoscope, 64) and use of high-field intraoperative MRI, 65) et al These are reported to increase the safety and reduce the risk of the endoscopic approach. Recently, an experimental feasibility study on robotic endonasal telesurgery was reported.…”
Section: Economicsmentioning
confidence: 99%
“…The new developed instrumentations include high definition 3D endoscopic system, 10) endoscopic augmented reality navigation system, 62) ultrasonography-assisted endoscope, 63) the indocyanine green fluorescence endoscope, 64) and use of high-field intraoperative MRI, 65) et al These are reported to increase the safety and reduce the risk of the endoscopic approach. Recently, an experimental feasibility study on robotic endonasal telesurgery was reported.…”
Section: Economicsmentioning
confidence: 99%
“…[114][115][116] With more clinical experience it may become an integral modality in routine intraoperative ultrasound examination of brain masses. [117][118][119][120] This has shown to be useful in principle and is likely to be evaluated further in the future. …”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…More recently, however, rigid transsellar probes developed specifically for the needs and constraints of pituitary surgery have been described . Furthermore, novel endoscopic and rigid probes with side‐facing transducers have enabled intrasellar visualization . Although these side‐facing probes offer superior resolution and fewer artifacts, their utilization is limited by the need to create a resection cavity prior to probe insertion and by unfamiliarity with nonintuitive imaging planes .…”
Section: Technical Backgroundmentioning
confidence: 99%
“…In a recent case series of 9 patients, however, a narrow probe with a side‐facing transducer and power Doppler capability was able to provide intrasellar visualization of pituitary macroadenomas with a higher resolution (.19 mm × .22 mm) than that available via T1‐weighted MRI (1 mm × 1 mm) and without the need to remove extra bone to accommodate the probe . A subsequent case report that used a similarly small endoscopic transducer revealed consistent visualization of tumors and surrounding anatomic landmarks and vasculature . Transcranial US through a frontal burr hole has also been used as an adjunct in transsphenoidal resections of pituitary macroadenomas and, in contrast to endonasal probes that compete with space required for surgical instrument access, provided visualization during the resection itself …”
Section: Ultrasound Applicationsmentioning
confidence: 99%